Existence of global weak solutions for a 3D Navier–Stokes–Poisson–Korteweg equations. Issue 4 (12th March 2018) - Yang, Jianwei; Wang, Zhengyan; Ding, Fengxia
Abstract : The purpose of this work is to study the global-in-time existence of weak solutions of a viscous capillary model of plasma expressed as a so-called Navier–Stokes–Poisson–Korteweg model for large data in three-dimensional space. Using the compactness argument, we prove the existence of global weak solutions in the classical sense to such system with a cold pressure.